Komposisi Senyawa Penyusun Minuman Sinom (curcuma domestica val.- tamarindus indica l.) - Ni Ketut Wiradnyani; Ni Made Wartini; Bambang Admadi Harsojuwono (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2014)
Sinom beverages analternative functional food. The ingredients are curcumin and young tamarin leaves, it is easily available, relatively in expensive expected that is consumed, it contains antioxidant compounds. This study aimed to identification of sinom beverages antioxidant compounds to treatment of some types of solvent fractions are: hexane, chloroform and ethylacetate in vitro. With GCMS and TLC analysis of method.Hexana fraction all egedly contains compounds: ar-tumeron (21,32%), tumeron (49,84%) and curlon (27,25%), cloroform fraction contains compounds: ar-tumeron (20,04%), tumeron (10%) and curlon (15,84%), etil asetat fraction contain compounds: ar-tumeron (19,98%), tumeron (24,52%) and curlon (16%.) and the water fraction contain compounds: 9-oktadecanoid fatty acids (69,43%), ascorbic acid (32,7%), Ribovlafin (37,1%), ar-tumeron (1,31%), tumeron (2,85%) and curlon (1,09%.),The results showed hexan, kloroform, etil asetat and water fraction of sinom beverages contains compound: 9-oktadecanoid fatty acids, ascorbic acid, Ribovlafin, ar-tumeron, tumeron and curlon.Keywords: Sinom beverage, compotition, solvent fraction